Evaluation of the Elderly's Environmental Practices Concerning Fall prevention at Governmental Elderly Homes in Baghdad City - Abdulridha, Maysoon; nagi, arkan (Iraqi National Journal of Nursing Specialties, 2016)
Objective :To evaluate elderly's environmental practices concerning fall prevention at governmental elderly care homes in Baghdad city. Methodology: A quazi- Experimental study was carried out in governmental elderly care homes at Baghdad city, during the period 1st, June 2014 to 30th November, 2014 , selected a purposive " Non – probability " sample of (40) elderly men and women aged (60) years old and over who were resident in governmental elderly care homes " Al Ceelakh and Al Sader elderly care homes", the data was collected through the use of constructed questionnaire that consist of (23) items, and interview technique was used to collect the data. Analysis of the data was done through the use of frequencies, percentages, relative sufficiency, mean of score and cut of point . Results: Results of finding of data analysis related to the study participants had benefits from the implementation of fall prevention upon elderly in elderly care homes and modification to their practices related environment risk factors. Recommendations: Emphasize on applying the fall prevention program in all elderly care homes, and their awareness toward the effect of risk factors and elderly falls.